Desiccation and Preculture Effects on Survival of Encapsulated Zygotic Embryos of Rubber (Hevea Brasiliensis Muel.-Arg) Following Liquid Nitrogen Exposure - Yap, Lip Vun (1998)
The effects of desiccation, sucrose as cryoprotectant and abscisic acid (ABA) as chemical ameliorant on the cryopreservation of Hevea zygotic embryos were evaluated using the alginate encapsulation method. The first part of the study was on the effects of desiccation on the survival of alginate-encapsulated Hevea zygotic embryos following liquid nitrogen exposure. The embryos need to be desiccated to at least 26% moisture content to enable some survival after exposure to liquid nitrogen. Embryos desiccated to moisture content of 14% and 18% gave comparatively higher survival after cryopreservation (42.5% and 47.5% respectively). Encapsulation of the embryos enhanced desiccation tolerance and desiccation was allowed even until 10% moisture content with some survival even though Hevea seeds are known to be recalcitrant. Encapsulation had broaden the window for cryopreservation by allowing the embryos to survive desiccation and cryopreservation at a broader range of moisture content compared to naked embryos done in previous work. However, a very low percentage of embryos developed into normal plantlets. The importance of sucrose preculture for cryopreservation of encapsulated Hevea embryos is also proven in this study. Sucrose preculture at low concentration of 0.3 M improved viability and survival before and after cryopreservation significantly to 70% and 60% respectively. Desiccation and freezing resistance were further enhanced when the encapsulated embryos were precultured on 0 . 5 M sucrose with viability as high as 82% (after cryopreservation). However, after twelve weeks culture, the percentage of survival after cryopreservation was maintained as when precultured on 0.3 M sucrose, with 1 4% and 1 6% moisture levels showing better results (51% and 59% respectively). Preculture with 0.5 M sucrose improved perculture of embryos developed into normal plantlet (as high as 35% and 32% survival before and after cryopreservation). As the concentration of sucrose preculture was increased further to 0.7 M and 0.9 M, the freezing tolerance of the embryos reduced considerably. A very low percentage of normal plantlet was obtained after cryopreservation (3 to 9%). Desiccation tolerance was also slightly reduced as indicated by lower survival before cryopreservation.